Searching for equity-centered change agents: An investigation of family and community engagement in teacher evaluation frameworks - Mayger, Linda K.; Provinzano, Kathleen (Education Policy Analysis Archives, 2022)
Federal legislation in the United States granted states freedom to alter formerly test-based teacher evaluation systems and situate family engagement as a key component in school improvement efforts. Concurrently, theorizing on family engagement has moved away from deficit characterizations and school-based involvement to an asset-based approach focused on equitable stakeholder collaborations committed to driving systemic change. Seeking to understand how states are characterizing exemplary teaching in terms of family and community engagement, the current study uses directed qualitative content analysis to examine 15 teacher evaluation rubrics or standards. The findings indicate that many evaluation systems were narrowly focused on the procedural aspects of teaching and teacher engagement with families was too often viewed merely as a mechanism to yield academic gains and meet legal requirements. The rubrics that explicitly stated that teachers should be culturally responsive provided a semblance of hope for pushing evaluative practices through the engagement barrier and into a space of collaboration that departs from dominant school-based approaches. These results have implications for the design of teacher evaluation policy and the furthering of equity-centered partnerships with families and communities.